Self-Oscillations Of Current In Silicon: Physical Principles, Mechanisms And Application (Texas Journal of Multidisciplinary Studies, 2024)
The article discusses self-oscillatory processes in silicon semiconductor devices, such as diodes and transistors, based on nonlinear effects of interaction of electric current and voltage. Particular attention is paid to the physical mechanisms of selfoscillations, including avalanche breakdown, thermal and electrical feedback, as well as their impact on the operation of silicon devices. Examples of the application of selfoscillatory modes in high-frequency signal generators and radio engineering devices are given. Methods for eliminating unwanted oscillations to ensure stable operation of circuits are also discussed.